INDIGENOUS IDENTITY, ORAL TRADITION, AND THE LAND IN THE POETRY OF OODGEROO NOONUCCAL, LUCI TAPAHONSO, AND HAUNANI-KAY TRASK - Woods, Amanda (East Carolina University, 2010)
This thesis is a postcolonial, ecocritical examination of the poetry of Oodgeroo Noonuccal, Luci Tapahonso, and Haunani-Kay Trask. It considers the use of poetry as a continuation of oral tradition, the poets' individual use of images of the natural world to depict the ties between their indigenous cultures and the land, and the way that this depiction reasserts the native identity of the culture they are representing.
Keywords: Literature; Australian Aboriginals; Ecocriticism; Indigenous cultures; Navajos; Poetry; Postcolonial; Poetry--Women authors; Women poets, American; Women poets, Australian; Oodgeroo Noonuccal, 1920-1993--Criticism and interpretation; Tapahonso, Luci, 1953- --Criticism and interpretation; Trask, Haunani-Kay--Criticism and interpretation; Oral tradition in literature; Folk poetry; Indian poetry; Hawaiian poetry; Aboriginal Australian poetry